Solution for on-demand network in smart campus - Honglei XU; Yuan ZHANG (Dianxin kexue)
The solution for China Telecom on-demand network in smart campus was introduced,and the demand and pain points of campus tenants in the campus environment were analyzed.Finally,the system composition,business model,as well as on-demand network features and advantages of the system in the campus environment were introduced.